Determination of cell water-relation parameters using the pressure probe: extended theory and practice of the pressure-clamp technique - Murphy, R; Smith, J (1998)
The aim of the present study was to develop and test an extended theory of the pressure-clamp technique that would allow the estimation of additional cell water-relation parameters using the pressure probe. It was assumed that intercellular water transport (vacuole → vacuole) occurs via a composite 'membrane' comprising the tonoplast, cytoplasm, plasma membrane, plasmodesmata and cell wall and that solute transport across the micropipette tip of the probe is dominated by convection. The extended theory allows the simultaneous estimation of cell volume (V), effective cell-sap osmotic pressure (σΠ0), compositemembrane hydraulic conductance (AL(P)) and the 'instantaneous' volume change (ν0) at the start of the pressure clamp. With an estimate of cell-sap osmotic pressure (Π0), the weighted-average reflection coefficient (σ) of the composite membrane may also be determined from an endosmotic pressure-clamp experiment. In principle, the cell volume before the clamp (V0) can be estimated as V0 = V + ν0, and the cell volumetric elastic modulus (ε) can be estimated as ε = -V0(ΔP/ν0), where ΔP (< 0) is the change in turgor pressure at t = 0. In practice it may be necessary to correct ν0 for transmembrane water flow when estimating V0 and ε. To test this theory, a previously described pressure-probe system was upgraded by incorporating a data-acquisition system to record turgor pressure, meniscus position, the penetration depth of the pressure-probe micropipette and the micropipette profile. An air bubble in the system allowed the turgor pressure to be clamped at a near-constant value. For mesophyll cells in leaf discs of Kalanchoe daigremontiana, the estimated mean value of V0 [(2.46 ± 0.24) x 10-13 m3] was in reasonable agreement with a value obtained from microscopy [(1.91 ± 0.10) x 10-13 m3]. When the positive correlation between ε and |ΔP| was taken into account, the parameter estimates obtained from pressure-clamp experiments were found to be consistent with those derived from pressurerelaxation experiments. The mean values of ε (1.4 ± 0.2 MPa) and L(P) [(5.76 ± 0.83) x 10-12 m s-1 Pa-1] were significantly different from previous estimates obtained with older leaves. Furthermore, in contrast to the estimated reflection coefficient of the plasma membrane/tonoplast (≃ 1), the mean value of σ obtained in the present study (0.62 ± 0.05) was significantly less than unity. This is attributed to a high hydraulic conductance and a low reflection coefficient of a symplastic pathway for intercellular water transport. The qualitative behaviour of L(P) and σ was consistent with a quasi-steady-state model of intercellular water transport that included volume flow through plasmodesmata. A quantitative description was obtained by fitting a simplified version of this model to the data. This led to the conclusion that significant volume flow can occur through plasmodesmata during pressure-clamp experiments, especially for small A and |ΔP|.